Sickle Cell Trait and Sickle Cell Disease: A Case Study - Shoumita Dasgupta (Association of American Medical Colleges, 2009)
Abstract This case presents a classic example of an African American individual who is heterozygous for sickle cell disease and who does not manifest any symptoms until he encounters extreme physical conditions. The case explores the initial presentation of sickle cell symptoms in a heterozygote, the assembly of a pedigree and calculation of genetic risk for transmission of the mutation, and the biochemical and genetic testing options that are available for diagnostic and preconception genetic testing in sickle cell disease. This case also covers the strategies governing newborn screening for hemoglobinopathies and their limitations; the genetic concept of compound heterozygosity as it relates to sickle cell and thalassemia mutations in the globin; and the ethical, legal, and societal ramifications of available types of testing strategies. Student evaluations were collected to examine reactions to the case material. In response to the question "What feature(s) most influenced your level of interest in the sickle cell disease case materials?", a majority of students selected "Motivation to learn concepts of clinical importance." General student comments included the following: "The questions posed were complex and this definitely encouraged discussion and debate more so than I have seen in other courses," "I have a much better understanding of the material after sitting with my group and discussing the issues," and "I would have liked more discussions as I feel I learn better in this format. I'm not a memorizer, so the more interactive a concept is administered to us, the better it is for me. I personally would rather learn lesser details but learn greater conceptual understanding of the material."